Type 2 inflammation in asthma and other airway diseases - Maspero, Jorge; Adir, Yochai; Al-Ahmad, Mona; Celis-Preciado, Carlos A.; Colodenco, Federico D.; Giavina-Bianchi, Pedro; Lababidi, Hani; Ledanois, Olivier; Mahoub, Bassam; Perng, Diahn-Warng; Vazquez, Juan C.; Yorgancioglu, Arzu (ERJ open research, 2022)
Chronic inflammatory airway diseases, including asthma, chronic rhinosinusitis, eosinophilic COPD and allergic rhinitis are a global health concern. Despite the coexistence of these diseases and their common pathophysiology, they are often managed independently, resulting in poor asthma control, continued symptoms and poor quality of life. Understanding disease pathophysiology is important for best treatment practice, reduced disease burden and improved patient outcomes. The pathophysiology of type 2 inflammation is driven by both the innate immune system triggered by pollutants, viral or fungal infections involving type 2 innate lymphoid cells (ILC2) and the adaptive immune system, triggered by contact with an allergen involving type 2 T-helper (Th2) cells. Both ILC2 and Th2 cells produce the type-2 cytokines (interleukin (IL)-4, IL-5 and IL-13), each with several roles in the inflammation cascade. IL-4 and IL-13 cause B-cell class switching and IgE production, release of pro-inflammatory mediators, barrier disruption and tissue remodelling. In addition, IL-13 causes goblet-cell hyperplasia and mucus production. All three interleukins are involved in trafficking eosinophils to tissues, producing clinical symptoms characteristic of chronic inflammatory airway diseases. Asthma is a heterogenous disease; therefore, identification of biomarkers and early targeted treatment is critical for patients inadequately managed by inhaled corticosteroids and long-acting β-agonists alone. The Global Initiative for Asthma guidelines recommend add-on biological (anti IgE, IL-5/5R, IL-4R) treatments for those not responding to standard of care. Targeted therapies, including omalizumab, mepolizumab, reslizumab, benralizumab, dupilumab and tezepelumab, were developed on current understanding of the pathophysiology of type 2 inflammation. These therapies offer hope for improved management of type 2 inflammatory airway diseases.